The Auditory Enhancement Effect is Not Reflected in the 80-Hz Auditory Steady-State Response - Carcagno, Samuele (Springer US, 2014)
The perceptual salience of a target tone presented in a multitone background is increased by the presentation of a precursor sound consisting of the multitone background alone. It has been proposed that this “enhancement” phenomenon results from an effective amplification of the neural response to the target tone. In this study, we tested this hypothesis in humans, by comparing the auditory steady-state response (ASSR) to a target tone that was enhanced by a precursor sound with the ASSR to a target tone that was not enhanced. In order to record neural responses originating in the brainstem, the ASSR was elicited by amplitude modulating the target tone at a frequency close to 80 Hz. The results did not show evidence of an amplified neural response to enhanced tones. In a control condition, we measured the ASSR to a target tone that, instead of being perceptually enhanced by a precursor sound, was acoustically increased in level. This level increase matched the magnitude of enhancement estimated psychophysically with a forward masking paradigm in a previous experimental phase. We found that the ASSR to the tone acoustically increased in level was significantly greater than the ASSR to the tone enhanced by the precursor sound. Overall, our results suggest that the enhancement effect cannot be explained by an amplified neural response at the level of the brainstem. However, an alternative possibility is that brainstem neurons with enhanced responses do not contribute to the scalp-recorded ASSR.